Balancing Performance and Brand Marketing Goals: A Synergistic Approach to Sustainable Growth - Jha, Ananya (Journal of Marketing Studies, 2024)
Purpose: The pursuit of sustainable growth in today's competitive landscape necessitates a delicate balancing act between performance marketing, focused on immediate conversions and ROI, and brand marketing, emphasizing long-term brand building and customer loyalty. Businesses face the pressure to drive immediate sales through performance marketing, yet also recognize the critical role of brand marketing in building long-term customer loyalty and resilience. This paper challenges the conventional view of performance and brand marketing as rivals. Instead, it proposes a paradigm shift: acknowledging them as additional forces. Methodology: The methodology used for attaining a balanced approach includes ideas and real life example from the Edtech industry to effectively incorporate both perspectives. By viewing them as interconnected gears in the growth engine, we can unlock synergistic potential. Findings: Performance marketing, often characterized by its focus on quantifiable metrics like conversions and return on investment (ROI), has become a dominant force in the marketing landscape Unique contributor to theory, policy and practice: Creating competition between brand building and performance marketing leads to a zero-sum game, where both strategies suffer and overall marketing impact diminishes.